2008
DOI: 10.4319/lo.2008.53.3.0997
|View full text |Cite
|
Sign up to set email alerts
|

Mass coral spawning: A natural large‐scale nutrient addition experiment

Abstract: A mass coral spawning event on the Heron Island reef flat in 2005 provided a unique opportunity to examine the response of a coral reef ecosystem to a large episodic nutrient addition. A post-major spawning phytoplankton bloom resulted in only a small drawdown of dissolved inorganic phosphorus (DIP minimum 5 0.37 mmol L 21 ), compared with almost complete removal of dissolved inorganic nitrogen (DIN) (minimum NO, suggesting that pelagic primary production is potentially N limited on the timescale of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
112
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 84 publications
(124 citation statements)
references
References 51 publications
(106 reference statements)
8
112
3
Order By: Relevance
“…These results agree with prior work, where increased concentrations of OM were quickly aerobically degraded by bacteria within minutes to hours (Ferrier-Pages et al, 2000) and enhanced GPP more than R Eyre et al, 2008). While some of this OM was likely degraded in the water column, previous experiments (e.g.…”
Section: The Response In Coral Reef Sediment Metabolism To Organic Masupporting
confidence: 83%
See 1 more Smart Citation
“…These results agree with prior work, where increased concentrations of OM were quickly aerobically degraded by bacteria within minutes to hours (Ferrier-Pages et al, 2000) and enhanced GPP more than R Eyre et al, 2008). While some of this OM was likely degraded in the water column, previous experiments (e.g.…”
Section: The Response In Coral Reef Sediment Metabolism To Organic Masupporting
confidence: 83%
“…Wild et al, 2004a;24 h) or coral spawn and phytodetritus (e.g. Eyre et al, 2008; 1 week), on coral reef sediment metabolism have shown a short-term increase in GPP / R, contrasting the results provided from short-term temperature studies on coral reef sediments, where GPP / R decreased (Trnovsky et al, 2016;24 h). Experimental additions of coral mucus from Acropora spp.…”
Section: Introductionmentioning
confidence: 54%
“…sediments can rapidly pick up organic matter that is then degraded over a longer time period), despite their function as biocatalytical filter systems (Wild et al 2004a(Wild et al ,c, 2008. This is supported by Eyre et al (2008), who demonstrated the buffer function of reef sediments for phosphorus. After a sedimentation event, organic matter may be adsorbed by the relatively large surface area of the porous carbonate grains , loading the porous matrix with degradable material like a sponge soaking up water.…”
Section: Discussionsupporting
confidence: 53%
“…Despite the observed seasonal variability in Symbiodinium population density, all corals maintained high gross productivity and organic matter release throughout the year, indicating high metabolic plasticity to seasonal variation in environmental conditions. For tropical coral reefs, it is widely accepted that N is the most limiting nutrient to coral primary productivity [19]. Phosphorus (P) may also be limiting to coral metabolism [47], particularly in the case of an imbalanced nutrient supply with excess inorganic N (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, corals have evolved strategies to exploit any source of inorganic N [18], enabling them to survive in oligotrophic tropical waters where N is the most limiting nutrient to primary productivity [19,20]. However, the abundance of symbiotic Symbiodinium within the coral host is limited by N concentrations [4,21].…”
Section: Introductionmentioning
confidence: 99%